Development of the Commercial Banking System in Afghanistan : Risks and Rewards - Charap, Joshua (IMF Working Papers; Working Paper ;, 2009)
Lending practices of commercial banks in Afghanistan were analyzed using CAMEL ratings. Statistically significant correlations were found: Banks with worse ratings (a) had more lending to domestic clients and (b) paid less tax. There was no statistically significant relationship between profits and total assets or between lending/assets versus profit/assets. Interviews of senior management of 8 banks accounting for about 90 percent of the commercial banking system corroborated evidence that poorly rated banks lend to domestic clients, whereas highly rated banks do not lend. Banks that lend extensively domestically engage in extra-judicial, non-traditional contract enforcement.